1984
DOI: 10.1111/j.1445-5994.1984.tb03580.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Angiotensin Converting Enzyme in Crohn's Disease, Ulcerative Colitis and Peptic Ulceration

Abstract: Serum angiotensin converting enzyme (ACE) activities were determined in patients with different types of inflammatory disease of the gastrointestinal tract, in patients with peptic ulcer, and in healthy volunteer subjects. ACE activity in serum was measured by its in vitro ability to cleave hippuric acid from the synthetic tripeptide hippuryl-L-histidyl-L-leucine. The hippuric acid so formed was quantified by high performance liquid chromatography and results are expressed as nmol hippuric acid produced/ml pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Additionally, an increased ACE inhibitor level is a common feature and a useful therapeutic marker in patients with sarcoidosis and hypercalcaemia 17. However, the significance of elevated ACE levels in patients with Crohn’s disease remains to be determined 18 19. This patient responded adequately to the prednisone treatment; therefore, we did not measure the serum ACE levels.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, an increased ACE inhibitor level is a common feature and a useful therapeutic marker in patients with sarcoidosis and hypercalcaemia 17. However, the significance of elevated ACE levels in patients with Crohn’s disease remains to be determined 18 19. This patient responded adequately to the prednisone treatment; therefore, we did not measure the serum ACE levels.…”
Section: Discussionmentioning
confidence: 98%
“…SACE levels when available are useful as the sensitivity ranges from 58% to 86% and specificity as high as 90% in sarcoidosis [23,24]. In contrast, many studies investigating SACE levels in Crohn's disease found it to be normal or low [23][24][25][26][27][28][29]. Seven of 8 cases reviewed that measured SACE had elevated levels (87.5%).…”
Section: Discussionmentioning
confidence: 99%